Efektivitas Penerapan Core Tax System dalam Meningkatkan Kepatuhan Wajib Pajak (Studi Kasus pada Kantor Pelayanan Pajak Pratama Jakarta) Tahun 2025) - Leman, Wahyu (Journal Business Inovation, Accounting and Management, 2025)
Digital transformation in the tax administration system is a strategic agenda of the Indonesian government to improve the effectiveness of tax management and taxpayer compliance. One of the main innovations is the implementation of the Core Tax System as an integrated system that manages the entire tax administration cycle digitally and in real-time (OECD, 2022). This study aims to analyze the effectiveness of the implementation of the Core Tax System in increasing taxpayer compliance at the Pratama Jakarta Tax Service Office (KPP) in 2025. The research uses a quantitative method with a survey approach. The research sample amounted to 120 taxpayers who were selected through simple random sampling techniques. Data was collected through a Likert scale-based questionnaire and analyzed using simple linear regression with the help of SPSS. The results of the study show that the implementation of the Core Tax System has a positive and significant effect on taxpayer compliance with a significance value of < 0.05 and a determination coefficient of 62%. These findings confirm that the digitalization of the tax system contributes significantly to increasing the formal and material compliance of taxpayers (Alm, 2019; Bird & Zolt, 2018).